Resilient cyber physical simulation for modified back-to-back converter with sliding mode control. (December 2021) - Senthilanthan, Karthikrajan; Annapoorani, K. Iyswarya
Abstract: This paper presents an approach on to the testing of cyber–physical controller-hardware in loop testing of modified back to back converter for three phase applications with sliding mode control. The proposed back-to-back converter is capable of feeding supply for two independent loads. The uncontrolled rectifier is utilised as front end converter and a modified back end converter is designed. The back converter has reduced semiconductor switches and rating of the DC link is reduced. The power electronics model is designed by using Multisim tool which is a pspice based electrical simulation software. The control terminals are interfaced with LabVIEW using co-simulation interface. The co-simulation technique involves controller on target control unit and the plant model in a real-time computer (Multisim). The DSP processor TMS320F2812 which has the control algorithm for controlling the plant model is connected with the NI Compact Date Acquisition (C-DAQ) module and is interfaced with LabVIEW, where the data acquisition takes place. The control strategy for back end control is based on integral sliding mode control. The performance analysis of the modified back-to-back converter is analysed with cyber physical hardware in loop and co-simulation framework.